HUBUNGAN SOPAN SANTUN DENGAN PRESTASI BELAJAR SISWA : HUBUNGAN SOPAN SANTUN DENGAN PRESTASI BELAJAR SISWA - WAHYUDDIN S. ADAM, MUH; MAULIDYAWANTI MOONTI , GUSFIN; SUKMAYANI, AYU (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This study uses qualitative research, which means that it aims to understand the phenomenon in depth by analyzing data that is not in the form of numbers but in the form of text, video, or audio. In this study, researchers start from existing data, use relevant theories as explanations, and end with the formation of a